(untitled) (ENTHYMEMA, 2022)
“The Imagined Province” investigates the shifts in what the “idea of the province” in the period of world war and the Russian revolution and civil war. I argue that the mental and emotional valence of Russia’s map changed markedly over these nine years as regionalist and provincial pride came into literary culture, urging a fresh view of central Russia outside the capital cities. This change of perspective emerges in essays, stories, and poetry throughout Central Russia, though this article focuses mainly on the Volga Region. Authors of many different political stripes contributed to this shift—among them, regionalists like Evgenii Chirikov and Nikolai Kliuev, pro-revolutionary socialists such as Maksim Gor’kii and Matvei Dudorov, and Bolsheviks like Aleksei Dorogoichenko and Fedor Bogorodskii. As the Bolsheviks regathered Russia, these provincial voices were overpowered by more prominent voices from the center. Nonetheless, they established a “usable history” that remains a substrate of Russian culture even today, challenging the simplistic binary juxtaposing “capital” and “province.”